NATIONAL HARMONY IN PAKISTAN: UNITY IN DIVERSITY THROUGH CULTURAL ASSIMILATION (Khairulummah, 2023)
National harmony is the integration of different ethnic, linguistic, religious groups in such a way that they retain their individual traits along with national unity. When the state takes care of their individuality, they serve the state to the best of their abilities and strengthen the notion of unity in diversity. All individuals are different and their diversity gives them identity. The different groups inside a state present plurality of cultures or multiculturalism. The basic objective of national harmony is to amalgamate different cultures and produce a new culture acceptable to all communities.
Keywords: National; cultures; harmony; ethnic linguistic